Infants' Discrimination of Consonants: Interplay Between Word Position and Acoustic Saliency. Issue 1 (2nd January 2016) - Archer, Stephanie L.; Zamuner, Tania; Engel, Kathleen; Fais, Laurel; Curtin, Suzanne
ABSTRACT: Research has shown that young infants use contrasting acoustic information to distinguish consonants. This has been used to argue that by 12 months, infants have homed in on their native language sound categories. However, this ability seems to be positionally constrained, with contrasts at the beginning of words (onsets) discriminated earlier. This study explores whether English-learning 12- and 20-month-olds discriminate coda consonants in word-final and word-medial positions. The 12-month-old group successfully discriminated place of articulation contrasts for voiced stops in word-final position, though not voiceless stops in either position, while the older infants discriminated place of articulation contrasts for both voiced and voiceless stops in both positions. This indicates that voiced stops may be more acoustically salient than voiceless, and that position influences discrimination. Our findings support the claim that infants build speech sound categories starting with more salient contrasts in strong positions, which expand to other positions over the course of development.